The Dynamism of the Social Literary and Hermeneutical Streams in Qurʾanic Classical and Modern Exegesis Studies - Selamat bin Amir; Ahmad Bazli Ahmad Hilmi; Mustaffa bin Abdullah; Muhamad Alihanafiah Norasid (Brill, 2024)
Al-Bayan Journal of Qur’an and Hadith Studies, Volume 22 Issue 2 Page (190–215)